Predicting Residential Property Values Around Landfill Neighbourhoods in Lagos, Nigeria - Akinjare, O. A.; Oloyede, S. A.; Ayedun, C. A.; Ajibola, M. A. (Mediterranean Journal of Social Sciences, 2011)
Some studies have proven landfills to negatively impact value of residential properties within kilometers of proximity while fewothers have generated mixed conclusions. This study establishes a predictive model for residential property values within 1 200mproximity to the four landfills in Lagos State by examining their varying sizes, operating status and history inclusive of diminutiontendencies. The relationship between each landfill and property values were measured based on interval of 300meters up to 1 200 metersin concentric rings.The resultant model validates the findings of the study that across the four landfill sites, increases in property values were evidentas distance away from the landfills increased indicating that residential houses in close proximity to the landfills suffered value loss.Property appreciation relative to distance averaged 5.75% within the concentric rings for all four landfills.The study suggested the closure of all landfils within residential areas and a relocation of such to uninhabited areas in the city’s outskirtin order to promote sustained value appreciation